(untitled) (International Journal of Environmental Sciences, 2025)
Background- Umbilical cord is a vital structure of fetal life. The growth of the umbilical cord increases during pregnancy, peaking at 32 weeks, plateauing till 34th week and then marginally declines, and hence constitutes an appropriate parameter for verifying the prediction of fetal growth pattern. Objectives- To correlate umbilical cord area and diameter with established fetal parameters (biparietal diameter, head circumference, femur length and abdominal circumference) in estimating gestational age and fetal weight. Methods- The study was a prospective hospital-based study. This study included 200 patients who will undergo USG imaging in our Department of Radiodiagnosis,Vinayaka Missions Kirupananda Variyar Medical College & Hospital,Salem for a time period of two years for obstetrics ultrasound scan from 14 weeks to 40 weeks of gestation. If the inclusion criteria was fulfilled, informed consent was taken, the patient was briefed about the procedure and relevant instructions were given to the patient. Results- The mean umbilical cord diameter as well as cross sectional increases steadily with gestational age from 14 weeks to 34 weeks and then it declines till 39 week of gestational age. Conclusion -There is a very strong correlation between HC, AC, EFW and UCD. Strong correlation was also observed between FL, BPD and UCD. There is also a very strong correlation between HC, AC, EFW and UCA. Strong correlation is observed between FL, BPD and UCA.